The Effectiveness of Cognitive Behavioral Therapy on Distress Tolerance and Psychological Hardiness in Adolescents Experiencing Parental Bereavement - Mahmodi , Aida; Hasanpor Abri , Maryam; Vakili , Santik; SamKhaniani, Eshagh; Moradi Vajargah, Ghazal (KMAN Counseling & Psychology Nexus, 2026)
The present study was conducted to determine the effectiveness of cognitive behavioral therapy on distress tolerance and psychological hardiness in adolescents experiencing parental bereavement. The research method was quasi-experimental with a pretest–posttest design and a control group. The statistical population of the present study consisted of adolescents experiencing parental bereavement who were referred to the Arsam Psychological Services and Counseling Center in the city of Tonekabon in 2026. First, the Barrett and Scott Grief Experience Questionnaire (1998) was distributed among all participants. Then, 30 individuals with moderate grief experience (scores between 68 and 102) were selected through purposive and convenience sampling methods and were randomly assigned to two groups: an experimental group of 15 participants and a control group of 15 participants. Data were collected using the Distress Tolerance Questionnaire and the Psychological Hardiness Questionnaire. Subsequently, cognitive behavioral therapy was implemented for the experimental group in 8 sessions of 90 minutes each. After the completion of the cognitive behavioral therapy sessions, posttests were administered to both the experimental and control groups. The findings indicated a significant difference between the mean pretest and posttest scores of the experimental and control groups in terms of distress tolerance and psychological hardiness. Therefore, cognitive behavioral therapy has an effect on distress tolerance and psychological hardiness in adolescents experiencing parental bereavement.